QUALITATIVE PHTOCHEMISTRY PROFILE OF WATERMELON (CITRULLUS VULGARIS SCHRAD) RIND EXTRACTS WITH DIFFERENT SOLVENTS - Hannah m, Angeline CHRISTIE; s, KRISHNAKUMARI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Introduction: Citrullus vulgaris Schrad. is known to contain bioactive compounds such as cucurbitacin, triterpenes, sterols and alkaloids, vitamins, minerals and has also proved to contain antioxidant and therapeutic properties. Objectives: The study focus to elucidate on the percentage of extractive yield and to screen the watermelon rind extracts using various solvents and hot aqueous extract for its phytochemical profile. Methods: The solvents used were methanol, ethanol, chloroform, petroleum ether, ethyl acetate, acetone and hot aqueous extracts. The rind samples were shade dried and powdered. It was then subjected to soxhlet extraction using the different solvents and pressurized hot water extraction. The obtained extracts were concentrated and screened for preliminary phytoconstituents using standard laboratory protocols. Results: The rind extracts with different solvents and pressurized hot water extract showed different yield percentages and on analysis, hot aqueous extract was found to have the highest extractive yield. The preliminary screening of the rind extracts with different solvents and pressurized hot water extract were tabulated and showed the presence and/or absence of various bioactive constituents including the primary and secondary metabolites. Conclusion: Thus, the phytochemical constituents such as the primary metabolites and the secondary metabolites and various other bioactive elements that are identifies are thought to be responsible for its antioxidant and therapeutic properties. Keywords: Citrullus vulgaris Schrad., Metabolites, Phytoconstituents, Soxhlet extraction, Yield percentage, Watermelon rind.